Critical Pedagogy in The French Language Classroom in Ghana: Challenges and Perspectives - Doreen Enyonam Esi Yegblemenawo; Stella Afi Makafui Yegblemenawo (Educational Considerations, 2025)
This study explores the role of critical pedagogy in developing 21st-century skills such as critical thinking, problem-solving, and communication (active participation in the classroom) among students. Grounded in Paulo Freire’s concept of critical pedagogy, this qualitative research draws insights from four focus group discussions involving 20 Ghanaian French language teachers. The study examines teachers’ perceptions and lived experiences in implementing critical pedagogy in their French language classrooms. Findings show that while teachers recognise the value of critical pedagogy, they face challenges in effectively applying these principles due to limited support and structural constraints, necessitating additional assistance. The study recommends strategies such as the integration of creative, learner-centred and interactive exercises to address these challenges. These recommendations aim to enhance the teaching-learning process and promote a more transformative classroom experience.
Keywords: critical pedagogy; social justice; French language classroom; Ghana